2020
DOI: 10.1042/bsr20192510
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a frame shift mutation in the CCDC151 gene in a Han-Chinese family with Kartagener syndrome

Abstract: Kartagener syndrome (KS), a subtype of primary ciliary dyskinesia (PCD), is characterized by bronchiectasis, chronic sinusitis, male infertility and situs inversus. KS is a genetically heterogeneous disease that is inherited in an autosomal recessive form; however, X-linked inheritance has also been reported. As of this writing [late 2020], at least 34 loci, most of which have known genes, have been reported in the literature as associating with KS. In the present study, we identified a frame shift mutation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Exome sequencing, a cost-saving measure, has been used in the genetic investigation of HTX [12][13][14]. Our previous study has successfully identified pathogenic variants in two Chinese families with SI phenotype via exome sequencing [15,16]. In this study, exome sequencing and Sanger sequencing detected the compound heterozygous variants, c.3426-1G>A and c.4306C>T (p. (Arg1436Trp)), in the dynein axonemal heavy chain 11 gene (DNAH11, NM_001277115.1) in a Han Chinese family with HTX and CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Exome sequencing, a cost-saving measure, has been used in the genetic investigation of HTX [12][13][14]. Our previous study has successfully identified pathogenic variants in two Chinese families with SI phenotype via exome sequencing [15,16]. In this study, exome sequencing and Sanger sequencing detected the compound heterozygous variants, c.3426-1G>A and c.4306C>T (p. (Arg1436Trp)), in the dynein axonemal heavy chain 11 gene (DNAH11, NM_001277115.1) in a Han Chinese family with HTX and CHD.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a total of seven likely loss-of-function variants in ODAD3 have been reported in PCD (Supplementary Table 2). The reported ODAD3 variants including three non-sense variants: p.(Gly309 * ) (Hjeij et al, 2014); p.(Ser409 * ) (Hjeij et al, 2014); p.(Glu109 * ) (Zhang et al, 2019); three frame-shifting variants: p.(Gly56Aspfs * 26) (Deng et al, 2020); p.(Lys77Leufs * 6) (Mani et al, 2020); p.(His199Argfs * 60) (Olm et al, 2019) and one splice site variant: c.244+1G>A (Monies et al, 2019). The only two hitherto reported female patients (10 week and 1 year-old, respectively) did not reach reproductive age.…”
Section: Discussionmentioning
confidence: 99%
“…DNA nanoballs were formed via rolling circle amplification using circular single‐stranded libraries and then loaded onto a sequencing chip. The captured exome library underwent high‐throughput sequencing on the BGISEQ‐500 (BGI, Shenzhen, China) platform in accord with the manufacturer's instructions 24 . Sequencing‐derived raw image files obtained were transformed into ‘raw data’ with BGISEQ‐500 base calling software.…”
Section: Methodsmentioning
confidence: 99%
“…After excluding synonymous variants, non‐exonic SNPs and non‐canonical splicing sites, non‐synonymous variants in the 42 PCD‐associated genes were selected 26 http://www.mutationtaster.org/), Sorting Intolerant from Tolerant (SIFT, http://sift.jcvi.org/), Polymorphism Phenotyping version 2 (PolyPhen‐2, http://genetics.bwh.harvard.edu/pph2/) and Berkeley Drosophila Genome Project/Splice Site Prediction by Neural Network (BDGP/NNSplice, http://www.fruitfly.org/seq_tools/splice.html 24 . Sanger sequencing of enrolled family members verified the identified potential causative variants with an ABI3500 sequencer (Applied Biosystems Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation